Successful treatment of fetal circular shunt using Indomethacin in Ebstein anomaly with early hydrops - Yubbu, Putri; Pang, Kah Yit; Koh, GT; Valayudham, Vairavan Ramesh (Malaysian Pediatric Cardiac Society, 2024)
Ebstein anomaly (EA) is a rare congenital malformation with a reported mortality of nearly 50% when diagnosed in utero. Factors associated with poorer outcomes include fetal hydrops and circular shunt (CS), which involves pulmonary regurgitation and excessive reversal flow across the ductus arteriosus (DA). Fetal CS causes systemic hypoperfusion, which is an essential hemodynamic consequence leading to fetal death. Transplacental non-steroidal anti-inflammatory drugs (NSAIDs), such as indomethacin, have been successfully used in Ebstein anomaly to induce fetal DA constriction and reduce the amount of CS. We report 2 cases of fetal with Ebstein anomaly with severe TR, functional pulmonary atresia and progressive CS across a widely patent DA and regurgitant pulmonary valve causing hydrops fetalis. The first fetus at 29 weeks had severe hydrops compared to the second fetus with early hydrops at 33 weeks of gestation. To mitigate the amount of CS and prolong pregnancy, both cases were started in-utero Indomethacin upon detection. Both mothers received a loading dose of oral Indomethacin 100mg BD and maintenance 25mg QID. The fetus, who was at 33 weeks gestation, responded well with complete resolution of fetal hydrops within two weeks of treatment. On the other hand, the first fetal case did not respond to the treatment despite optimizing the dose with the development of oligohydramnios; hence, treatment was withheld. The second fetus was successfully delivered at 37 weeks gestation via caesarean section with a birth weight of 2.8 kg and a good Apgar score. In conclusion, prenatal Indomethacin therapy successfully constricted the ductus arteriosus, resolving the circular shunt in Ebstein anomaly with early hydrops, thereby averting severe morbidity and mortality. Close dose adjustments were necessary to avoid anhydramnios and fetal renal injury, as well as a careful selection of patients who would benefit from this early antenatal treatment.